Method for manufacturing a reflective mask blank and a reflective mask
The reflective mask blank with a tantalum-silicon-nitrogen back conductive film addresses the challenge of minimizing defects during electrostatic chucking by optimizing nitrogen and silicon content, achieving effective conductivity and surface smoothness.
Patent Information
- Application Number
- JP2022139059
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2022-09-01
- Publication Date
- 2025-04-28
- Estimated Expiration
- 2042-09-01
AI Technical Summary
The back conductive film in reflective mask blanks faces challenges in maintaining low sheet resistance and surface roughness while minimizing defects during attachment and detachment from the electrostatic chuck stage, particularly due to issues with tantalum nitride films.
A reflective mask blank with a back conductive film composed of tantalum (Ta), silicon (Si), and nitrogen (N), where the nitrogen content is between 18 atom % and 35 atom %, and the silicon content is adjusted to maintain a sheet resistance below 500Ω/□ and surface roughness of 0.5 nm or less, thereby reducing the risk of defects during electrostatic chucking.
The proposed solution effectively reduces the occurrence of defects when attaching and detaching the reflective mask from the electrostatic chuck stage, while maintaining the necessary electrical conductivity and surface smoothness of the back conductive film.
Smart Images

Figure 0007669321000001 
Figure 0007669321000002 
Figure 0007669321000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a reflective mask blank, which is a material for a reflective mask used in the manufacture of semiconductor devices such as LSIs, and a method for manufacturing a reflective mask using the reflective mask blank. [Background technology]
[0002] In the manufacturing process of semiconductor devices (semiconductor device), photolithography technology is repeatedly used, in which exposure light is irradiated onto a transfer mask, and the circuit pattern formed on the mask is transferred onto a semiconductor substrate (semiconductor wafer) via a reduced projection optical system. Conventionally, the wavelength of the exposure light has been mainly 193 nm using argon fluoride (ArF) excimer laser light, and a process called multi-patterning, which combines exposure processes and processing processes multiple times, has been used to ultimately form patterns with dimensions smaller than the exposure wavelength.
[0003] However, as the device patterns continue to become finer, the formation of even finer patterns is becoming necessary, and thus EUV lithography technology using EUV (Extreme Ultra Violet) light, which has a shorter wavelength than ArF excimer laser light, as exposure light has been developed. EUV light is light with a wavelength of, for example, about 10 to 20 nm, more specifically, light with a wavelength of about 13.5 nm. This EUV light has extremely low permeability to materials, and conventional transmission type projection optical systems and masks cannot be used, so reflective optical elements are used. Therefore, reflective masks are also used as masks for pattern transfer. In general, a reflective mask is formed by forming a multilayer reflective film that reflects EUV light on a substrate, and forming a patterned absorber film that absorbs EUV light on the multilayer reflective film. On the other hand, a mask in a state before patterning the absorber film (including a state in which a resist film is formed) is called a reflective mask blank, and this is used as a material for a reflective mask.
[0004] The reflective mask blank generally has a basic structure including a low thermal expansion substrate, a multilayer reflective film formed on one of the two main surfaces of the substrate to reflect EUV light, and an absorber film formed thereon to absorb EUV light. As the multilayer reflective film, a multilayer reflective film is usually used in which molybdenum (Mo) layers and silicon (Si) layers are alternately stacked to obtain a necessary reflectance for EUV light. Furthermore, a ruthenium (Ru) film is formed on the multilayer reflective film as a protective film for protecting the multilayer reflective film. In addition, as the absorber film, tantalum (Ta) or the like, which has a relatively large extinction coefficient value for EUV light, is used (JP Patent Publication 2002-246299 (Patent Document 1), etc.). Meanwhile, a backside conductive film is formed on the other main surface of the substrate. As the backside conductive film, a metal nitride film has been proposed for electrostatic chucking, and mainly includes nitride films of chromium (Cr), tantalum (Ta), molybdenum (Mo) or silicon (Si). [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2002-246299 A Summary of the Invention [Problem to be solved by the invention]
[0006] The backside conductive film is required to have low sheet resistance and small surface roughness for electrostatic chucking, and also to reduce the occurrence of defects when the mask of the exposure tool is attached and detached. When tantalum (Ta) is used for the backside conductive film, a small amount of nitrogen may be added to the film to reduce the sheet resistance and surface roughness. In addition, adding nitrogen to the film to nitride it is also effective in reducing the occurrence of defects when the mask of the exposure tool is attached and detached. However, in a film with a low degree of nitridation and many metal bonds of tantalum (Ta) remaining, when the film is in contact with another material and a force is applied to the substrate, so-called rubbing occurs, and defects may occur when the electrostatic chuck stage of the exposure tool is attached and detached. On the other hand, when a large amount of nitrogen is added to the film, rubbing marks are unlikely to occur, but the sheet resistance of the film increases, making electrostatic chucking impossible, and furthermore, the film stress due to the crystal growth of tantalum nitride is likely to increase, and the film surface roughness increases, so that the possibility of defects occurring increases.
[0007] The present invention has been made to solve the above-mentioned problems, and has an object to provide a reflective mask blank having a back surface conductive film that is less likely to cause defects when attached to and detached from an electrostatic chuck stage while maintaining the conductivity and surface roughness required for a back surface conductive film, and a method for manufacturing a reflective mask using the reflective mask blank. [Means for solving the problem]
[0008] The inventors of the present application have conducted intensive studies to solve the above problems, and have found that a backside conductive film containing tantalum (Ta), silicon (Si) and nitrogen (N), with a nitrogen content of 18 atomic % or more and less than 35 atomic %, and a layer in which CSi / (CTa+CSi) is 3% or more and less than 50%, where CSi is the silicon content in atomic % and CTa is the tantalum content in atomic %, makes the backside conductive film easily microcrystalline and amorphous, and suppresses increases in film stress and surface roughness, etc. If the silicon (Si) content is too high, the sheet resistance when the film is nitrided is likely to be high, but by setting the content within the above range, the sheet resistance can be reduced, and by setting the nitrogen content within the above range, the presence ratio of metal bonds in tantalum can be suppressed, resulting in a film quality that is less likely to have scratches, and the risk of scratches occurring when attaching and detaching the chuck stage can be reduced, leading to the present invention.
[0009] Accordingly, the present invention provides the following reflective mask blank and method for producing a reflective mask.
[0010] [Concept 1] The reflective mask blank according to the present invention comprises: A substrate; a multilayer reflective film provided on one surface of the substrate and reflecting at least EUV light; a back surface conductive film provided on the other surface of the substrate; Equipped with The back surface conductive film may have a layer having a thickness of 50 nm or more and less than 80 nm, containing tantalum (Ta), silicon (Si) and nitrogen (N), having a nitrogen content of 18 atomic % or more and less than 35 atomic %, and where, when the silicon content in atomic % is CSi and the tantalum content in atomic % is CTa, CSi / (CTa+CSi) is 3% or more and less than 50%.
[0011] [Concept 2] In the reflective mask blank in concept 1, The back surface conductive film is a first layer having a thickness of 50 nm or more and less than 80 nm, containing tantalum (Ta), silicon (Si) and nitrogen (N), the nitrogen content being 18 atomic % or more and less than 35 atomic %, and where the silicon content is CSi in atomic % and the tantalum content is CTa in atomic %, CSi / (CTa+CSi) is 3% or more and less than 50%; a second layer having a thickness of 3 nm or more and less than 10 nm, containing tantalum (Ta), silicon (Si), nitrogen (N) and oxygen (O), and having a total content of nitrogen and oxygen of 40 atomic % or more; may have the following structure:
[0012] [Concept 3] In the reflective mask blank in concept 2, the first layer is provided on the other surface of the substrate; The second layer may be provided on the other surface of the first layer.
[0013] [Concept 4] In the reflective mask blank in concept 1, The back surface conductive film may contain only tantalum (Ta), silicon (Si) and nitrogen (N).
[0014] [Concept 5] In the reflective mask blank according to concept 1 or 4, The back surface conductive film may have only a layer having a thickness of 50 nm or more and less than 80 nm, containing tantalum (Ta), silicon (Si) and nitrogen (N), having a nitrogen content of 18 atomic % or more and less than 35 atomic %, and where, when the silicon content in atomic % is CSi and the tantalum content in atomic % is CTa, CSi / (CTa+CSi) is 3% or more and less than 50%.
[0015] [Concept 6] In the reflective mask blank according to concept 2 or 3, the first layer contains only tantalum (Ta), silicon (Si) and nitrogen (N); The second layer may include only tantalum (Ta), silicon (Si), nitrogen (N) and oxygen (O).
[0016] [Concept 7] In the reflective mask blank according to concept 2, 3 or 6, The rear surface conductive film may include only the first layer and the second layer.
[0017] [Concept 8] In any one of concepts 1 to 7, the reflective mask blank further comprises: The back surface conductive film is Sheet resistance is 500Ω / □ or less. The surface roughness (Sq) of the film is 0.5 nm or less. When the change in warpage (ΔTIR) after forming the back surface conductive film relative to the warpage before forming the back surface conductive film is taken as a reference and expressed as plus (+) when it is a change in a concave direction and as minus (-) when it is a change in a convex direction, ΔTIR, which is an index of film stress when the back surface conductive film is formed on the substrate, may be -0.4 to -1.2 um.
[0018] [Concept 9] The method for manufacturing a reflective mask according to the present invention includes the steps of: It may be manufactured using a reflective mask blank according to any one of concepts 1 to 8. Effect of the Invention
[0019] By employing the rear surface conductive film provided in Concept 1 above, it is possible to provide a reflective mask blank having a rear surface conductive film that has good electrical conductivity, surface smoothness, and is resistant to abrasion and therefore is less likely to develop defects when attached to or detached from the electrostatic chuck stage. [Brief description of the drawings]
[0020] [Figure 1] FIG. 1 is a cross-sectional view showing an example of a reflective mask blank according to an embodiment of the present invention. [Diagram 2] FIG. 2 is a cross-sectional view showing another example of a reflective mask blank according to an embodiment of the present invention. [Diagram 3]FIG. 2 is a cross-sectional view showing an embodiment of the reflective mask blank according to the present invention, further comprising a hard mask film, a reflectance reducing layer, a protective film, etc. [Figure 4] FIG. 2 is a cross-sectional view showing an aspect in which an absorber film is patterned in a reflective mask blank according to an embodiment of the present invention. [Diagram 5] FIG. 1 is a cross-sectional view showing an embodiment of a reflective mask blank according to the present invention, in which a protective film, a resist film, etc. are provided. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0021] The embodiments of the present invention will be described in further detail below. The reflective mask blank (EUV mask blank) of this embodiment is used as a material for a reflective mask (EUV mask) used in EUV lithography using EUV light as exposure light. The reflective mask blank can be obtained by forming an absorber film on a film-attached substrate for a reflective mask blank, and further forming other films as necessary. The wavelength of the EUV light used in EUV lithography using EUV light as exposure light is 13 to 14 nm, and is usually light with a wavelength of about 13.5 nm.
[0022] As shown in FIG. 1 as an example, the reflective mask blank of the present embodiment at least comprises a substrate 10, a multilayer reflective film 20 that reflects EUV light and is formed on one of the two main surfaces of the substrate 10 (the upper surface in FIG. 1), preferably in contact with the substrate 10, and a back conductive film 30 that is formed on the other of the two main surfaces (the lower surface in FIG. 1), preferably in contact with the substrate 10. The reflective mask blank of the present invention also includes an embodiment in which a protective film 50 (see FIGS. 3 to 5) and an absorber film 70 (see FIGS. 1 to 5) are further provided on the multilayer reflective film 20. In addition, a hard mask film 110 (see FIG. 3) may be provided. From a reflective mask blank having an absorber film 70, a reflective mask having an absorber pattern (pattern of the absorber film 70) can be manufactured by patterning the absorber film 70 (see FIG. 4).
[0023] The substrate 10 preferably has low thermal expansion characteristics for use in EUV light exposure, and has a thermal expansion coefficient of, for example, ±2×10 -8 / °C, preferably within ±5×10 -9 It is preferable that the material is made of a material having a temperature within the range of 100°C / °F. Such a material is titania-doped quartz glass (SiO 2 -TiO 2 Glass-based glass, etc. are examples of the substrate 10. The substrate 10 preferably has a sufficiently flattened surface, and the surface roughness of the main surface of the substrate 10 is preferably 0.5 nm or less, particularly 0.2 nm or less, in terms of Sq value. Such a surface roughness can be obtained by polishing the substrate 10, etc. In the present embodiment, the size of the substrate 10 is not particularly limited, but for example, a substrate called a 6025 substrate, which is 6 inches square and 0.25 inches thick as specified in the SEMI standard, is suitable, and when the SI unit system is used, it is usually expressed as a substrate with a 152 mm square and a 6.35 mm thickness. The substrate 10 may have a layer such as a flattening layer on the surface.
[0024] The backside conductive film 30 is composed of tantalum (Ta), silicon (Si) and nitrogen (N). If the silicon content is CSi in atomic % and the Ta content is CTa in atomic %, then CSi / (CTa+CSi) is preferably 3% or more and less than 50%, and more preferably 5% or more and less than 20%. By adding a certain amount of silicon (Si), the film quality of the conductive film tends to become microcrystalline or amorphous, and an effect of suppressing increases in film stress and surface roughness can be obtained. If the silicon (Si) content is too high, the sheet resistance tends to increase when the film is nitrided.
[0025] The nitrogen content is preferably 18 atomic % or more and less than 35 atomic %, and more preferably 20 atomic % or more and less than 25 atomic %. By adjusting the nitrogen content to a predetermined amount and suppressing the abundance ratio of Ta metal bonds, the film becomes less susceptible to scratches, the risk of defects occurring when attaching and detaching the chuck stage is reduced, and the sheet resistance becomes 500 Ω / □ or less at a film thickness of less than 80 nm, enabling good adsorption by an electrostatic chuck.
[0026] The nitrogen content of the back surface conductive film 30 consisting of tantalum (Ta), silicon (Si) and nitrogen (N) may be determined using a narrow spectrum of XPS analysis as an index, and in the Ta 4f bond peak detected near a bond energy of 20 to 24 eV, the apex position of the peak is preferably greater than 22.5 eV and less than 23.0 eV, and more preferably greater than 22.6 eV and less than 22.9 eV.
[0027] The back surface conductive film 30 may have a layer (second layer) 32 made of tantalum, silicon, nitrogen and oxygen in addition to the above-mentioned layer (first layer) 31 made of tantalum, silicon and nitrogen, and may have a multilayer structure (see Figs. 2, 4 and 5). The degree of oxynitridation of the second layer 32 made of tantalum, silicon, nitrogen and oxygen is preferably higher than that of the first layer 31 made of tantalum, silicon and nitrogen. The second layer 32 is preferably present on the surface of the back surface conductive film 30 on the side separated from the substrate 10 (the lower side in Fig. 2). In this case, the first layer 31 may be provided on the other surface (lower surface) of the substrate 10, and the second layer 32 may be provided on the other surface (lower surface) of the first layer 31. Even in the case of a multilayer structure, the total thickness of the back surface conductive film 30 is preferably 40 to 100 nm, more preferably 60 to 80 nm. The thickness of the second layer 32 is preferably 20 nm or less, more preferably 10 nm or less.
[0028] In the present application, the back surface conductive film 30 or the first layer 31 containing only tantalum (Ta), silicon (Si), and nitrogen (N) means that the back surface conductive film 30 contains tantalum (Ta), silicon (Si), nitrogen (N), and inevitable impurities. Also, the second layer 32 containing only tantalum (Ta), silicon (Si), nitrogen (N), and oxygen (O) means that the second layer 32 contains tantalum (Ta), silicon (Si), nitrogen (N), and oxygen (O), and inevitable impurities.
[0029] The film stress of the back conductive film 30 is preferably the same as that of the surface on which the back conductive film 30 and the multilayer reflective film 20 are formed. The change amount ΔTIR of the surface shape (warpage) of the substrate 10 after the film is formed on the main surface on which the film is formed, compared to the warpage before the film is formed, can be used as an index. In this application, ΔTIR is expressed as a plus (+) when the change in the substrate shape after the film is formed is a change in a concave direction, and a minus (-) when the change is a convex direction, compared to the warpage before the film is formed on the surface on which the film is formed. In other words, it is expressed as a plus (+) when the film has tensile stress, and a minus (-) when the film has compressive stress. The warpage can be applied to a warpage within a range of 142 mm square with one side centered on the center of the main surface of the substrate 10. Here, the change amount (ΔTIR) of the warpage is expressed as a plus (+) when the change in the warpage after the film is formed is a change in a concave direction, compared to the warpage before the film is formed, and a minus (-) when the change is a convex direction, based on the main surface on which the back conductive film 30 is formed. That is, when the film has a tensile stress, it is positive, and when the film has a compressive stress, it is negative (-). ΔTIR is preferably set to -0.4 um to -1.2 um, and more preferably set to -0.4 um to -1.0 um.
[0030] In addition to the above characteristics, the backside conductive film 30 is also required to be less susceptible to defects when the electrostatic chuck plate is attached and detached. Examples of indicators that indicate the likelihood of defects occurring during attachment and detachment include a nano-scratch test using a diamond tip, a method of pressing a file-like material such as Steel Wool against the film surface and rubbing it to observe the surface condition, and a method of making scratch marks on a cross-hatch and then attaching and peeling off tape to check the film peeling condition.
[0031] In order to prevent defects from occurring when attaching and detaching the electrostatic chuck plate, the backside conductive film 30 is preferably composed of tantalum, silicon, and nitrogen, and the silicon and nitrogen are preferably adjusted to a predetermined amount. When the silicon content is CSi in atomic % and the tantalum content is CTa in atomic %, CSi / (CTa+CSi) is preferably 3% or more and less than 50%, and more preferably 5% or more and less than 20%. By adding a predetermined amount of Si, the film quality of the conductive film tends to become microcrystalline or amorphous, and an effect of suppressing increases in film stress and surface roughness can be obtained. If the silicon content is too high, the sheet resistance tends to increase when the film is nitrided.
[0032] The warpage of a reflective mask blank varies depending on the composition and physical properties of the film, but for example, when the size of the substrate 10 is a 152 mm square main surface and a thickness of 6.35 mm (when the substrate 10 is a 6025 substrate), it is preferable that the film-coated substrate 10 for a reflective mask blank has a warpage change (ΔTIR) between (1) the warpage of one main surface (the main surface on the side on which the multilayer reflective film 20 or the multilayer reflective film 20 and the protective film 50 are formed) before the multilayer reflective film 20 or the multilayer reflective film 20 and the protective film 50, and the back surface conductive film 30 are formed on the substrate 10, and (2) the warpage of one main surface (the main surface on the side on which the multilayer reflective film 20 or the multilayer reflective film 20 and the protective film 50 are formed) in a state in which the multilayer reflective film 20 or the multilayer reflective film 20 and the protective film 50, and the back surface conductive film 30 have been formed on the substrate 10, within a range of −0.3 to +0.3 μm. Therefore, it is preferable that the absolute value of the change in warpage (ΔTIR) of the substrate 10 before and after forming only the multilayer reflective film 20 or the multilayer reflective film 20 and the protective film 50 on the substrate 10 is approximately the same as the absolute value of the change in warpage (ΔTIR) of the substrate 10 before and after forming only the back surface conductive film 30 on the substrate 10. Here, the warpage can be within a range of 142 mm square on one side centered on the center of the main surface of the substrate 10. Note that the change in warpage (ΔTIR) here indicates the change in warpage after the film is formed with respect to the warpage before the film is formed, with the main surface on which the multilayer reflective film 20 or the multilayer reflective film 20 and the protective film 50 are formed being used as a reference, and a change in a concave direction is indicated as plus (+), and a change in a convex direction is indicated as minus (-).
[0033] Considering the thermal history in the processing step into a reflective mask, the reflective mask blank is usually subjected to a heat treatment in advance. In general, the higher the heat treatment temperature, the lower the reflectance of the multilayer reflective film 20, so the heat treatment temperature is preferably 150° C. or less. Therefore, it is preferable that the film-coated substrate for a reflective mask blank has a change in warpage (ΔTIR) between (1) the warpage of one of the main surfaces (the main surface on which the multilayer reflective film 20 or the multilayer reflective film 20 and the protective film 50 are formed) before the multilayer reflective film 20 or the multilayer reflective film 20 and the protective film 50, and the back surface conductive film 30 are formed on the substrate 10, and (2) the warpage of one of the main surfaces (the main surface on which the multilayer reflective film 20 or the multilayer reflective film 20 and the protective film 50 are formed) in a state in which the multilayer reflective film 20 or the multilayer reflective film 20 and the protective film 50, and the back surface conductive film 30 are formed on the substrate 10 and heat treatment is performed at 150° C. for 10 minutes, within a range of −0.3 to +0.3 μm.
[0034] Since the back conductive film 30 is a film used for electrostatically chucking a reflective mask to an exposure device, electrostatic chucking is possible if the sheet resistance (RS) is 500 Ω / □ or less, but it is more preferable that it is 250 Ω / □ or less, or even 100 Ω / □ or less.
[0035] From the viewpoint of suppressing particle generation during attachment and detachment of electrostatic chucking, the surface roughness Sq (root mean square height (ISO 25178)) of the back surface conductive film 30 is preferably smaller, and is preferably 0.5 nm or less, and more preferably 0.3 nm or less. As a measurement method, for example, measurement may be performed over an area of 1 μm square using an atomic force microscope (AFM). Large surface roughness is not preferable because it increases the possibility of defects occurring.
[0036] The back surface conductive film 30 may be formed before forming the multilayer reflective film 20, or may be formed after forming all the films on the multilayer reflective film 20 side of the substrate 10. Alternatively, after forming a portion of the films on the multilayer reflective film 20 side of the substrate 10, the back surface conductive film 30 may be formed, and then the remaining films on the multilayer reflective film 20 side of the substrate 10 may be formed.
[0037] The back surface conductive film 30 can be formed by a sputtering method in which power is supplied to a target, the atmospheric gas is turned into plasma (ionized) by the supplied power, and the target is irradiated with an ion beam sputtering method. Examples of the sputtering method include a DC sputtering method in which a direct current voltage is applied to the target, and an RF sputtering method in which a high frequency voltage is applied to the target. The sputtering method is a film formation method in which a voltage is applied to the target with a sputtering gas introduced into a chamber, the gas is ionized, and the sputtering phenomenon caused by the gas ions is utilized. In particular, the magnetron sputtering method is advantageous in terms of productivity. The DC sputtering method also includes a pulse sputtering method in which a negative bias applied to the target is reversed for a short time to prevent the target from being charged up.
[0038] The back surface conductive film 30 can be formed by a sputtering method using, for example, a sputtering device capable of mounting one or more targets. Specifically, a target made of silicon and tantalum, a silicon (Si) target, a tantalum (Ta) target, or the like is used as the target, and a rare gas such as helium (He) gas, argon (Ar) gas, krypton (Kr) gas, or xenon (Xe) gas, and nitrogen gas (N 2 Gas containing nitrogen, and oxygen gas (O 2 The gas may be formed using an oxygen-containing gas such as .
[0039] In the rear surface conductive film 30, the desired composition can be achieved by appropriately adjusting the power applied to the target (and the ratio between targets when multiple types of targets are used), the flow rate of the reactive gas (and the ratio between reactive gases when multiple types of reactive gases are used), etc.
[0040] The multilayer reflective film 20 is a film that reflects EUV light, which is exposure light, in a reflective mask. The multilayer reflective film 20 is a multilayer film in which layers of low refractive index material and layers of high refractive index material are alternately laminated. For EUV light with an exposure wavelength of 13 to 14 nm, for example, a Mo / Si periodic laminate film in which molybdenum (Mo) layers 22 and silicon (Si) layers 21 are alternately laminated for about 40 periods (40 layers of each) to 60 periods (60 layers of each) is used. The multilayer reflective film 20 usually has a film thickness of about 280 to 350 nm. A SiN layer may be formed between the Mo layer and the Si layer.
[0041] Methods for forming the multilayer reflective film 20 include a sputtering method in which power is supplied to a target, the atmospheric gas is turned into plasma (ionized) by the supplied power, and sputtering is performed, and an ion beam sputtering method in which an ion beam is irradiated onto the target. As a sputtering method, magnetron sputtering is particularly advantageous in terms of productivity. The power applied to the target may be DC or RF, and DC also includes pulse sputtering in which a negative bias applied to the target is reversed for a short period of time to prevent the target from charging up.
[0042] The multilayer reflective film 20 can be formed by a sputtering method using, for example, a sputtering device capable of mounting multiple targets. Specifically, the multilayer reflective film 20 can be formed by using, as the target, a molybdenum (Mo) target for forming a layer containing molybdenum (Mo) and a silicon (Si) target for forming a layer containing silicon (Si), and by using, as the sputtering gas, a rare gas such as helium (He) gas, argon (Ar) gas, krypton (Kr) gas, or xenon (Xe) gas. The sputtering may also be reactive sputtering using a reactive gas. In this case, for example, when forming a film containing nitrogen (N), nitrogen gas (N 2 A nitrogen-containing gas such as a nitrogen-containing gas (e.g., 1,2-dinitrogen fluoride gas) may be used in combination with a rare gas.
[0043] When forming a layer containing multiple elements, the power applied to the target (and the ratio between targets when multiple types of targets are used), the flow rate of the reactive gas (and the ratio between reactive gases when multiple types of reactive gases are used), etc. can be appropriately adjusted to obtain the desired composition, crystallinity, and other physical properties.
[0044] An absorber film 70 may be formed on the multilayer reflective film 20. The absorber film 70 is a film that absorbs EUV light, which is the exposure light, to reduce the reflectance of the exposure light, and in a reflective mask, a transfer pattern is formed by the difference in reflectance between a portion where the absorber film 70 is formed and a portion where the absorber film 70 is not formed. The absorber film 70 may be formed on the multilayer reflective film 20 in contact with the multilayer reflective film 20, or may be provided on the multilayer reflective film 20 via a protective film 50 (see FIGS. 3 to 5) described later.
[0045] The material of the absorber film 70 is not limited as long as it absorbs EUV light and can be patterned. Examples of the material of the absorber film 70 include materials containing tantalum (Ta) or chromium (Cr). The material containing tantalum or chromium may contain oxygen (O), nitrogen (N), carbon (C), boron (B), and the like. Examples of the material containing tantalum (Ta) include a Ta element, and tantalum compounds such as TaO, TaN, TaON, TaC, TaCN, TaCO, TaCON, TaB, TaOB, TaNB, TaONB, TaCB, TaCNB, TaCOB, and TaCONB. Examples of the material containing Cr include a Cr element, and chromium compounds such as CrO, CrN, CrON, CrC, CrCN, CrCO, CrCON, CrB, CrOB, CrNB, CrONB, CrCB, CrCNB, CrCOB, and CrCONB.
[0046] The absorber film 70 can be formed by sputtering, and magnetron sputtering is preferable. Specifically, the absorber film 70 can be formed by sputtering using a metal target such as a chromium (Cr) target or a tantalum (Ta) target, or a metal compound target such as a chromium compound target or a tantalum compound target (a target containing a metal such as Cr or Ta and oxygen (O), nitrogen (N), carbon (C), boron (B), or the like) as a sputtering gas, using a rare gas such as helium (He) gas, argon (Ar) gas, krypton (Kr) gas, or xenon (Xe) gas, or by reactive sputtering using a reactive gas such as an oxygen-containing gas, a nitrogen-containing gas, or a carbon-containing gas together with a rare gas. The thickness of the absorber film 70 is not particularly limited, but is usually about 30 to 90 nm.
[0047] It is preferable to form a protective film 50 between the multilayer reflective film 20 and the absorber film 70, preferably in contact with the multilayer reflective film 20, and more preferably in contact with both the multilayer reflective film 20 and the absorber film 70 (see Figs. 3 to 5). The protective film 50 is also called a capping layer, and is provided to protect the multilayer reflective film 20 when forming a pattern on the absorber film 70 thereon, when correcting the pattern of the absorber film 70, etc.
[0048] The material of the protective film 50 is preferably a material containing ruthenium (Ru). As the material containing ruthenium (Ru), ruthenium (Ru) alone, or a compound in which niobium (Nb) or zirconium (Zr) is added to ruthenium (Ru) is preferably used. The thickness of the protective film 50 is usually 5 nm or less, and particularly preferably 4 nm or less. The lower limit of the thickness of the protective film 50 is usually 2 nm or more.
[0049] The protective film 50 can be formed by a sputtering method such as an ion beam sputtering method or a magnetron sputtering method, similarly to the multilayer reflective film 20. The protective film 50 can be formed by a sputtering method using a sputtering device capable of mounting one or more targets, specifically, by sputtering using a ruthenium (Ru) target, or a ruthenium (Ru) target to which niobium (Nb), zirconium (Zr), or the like is added, and a target of one or more elements selected from niobium (Nb) and zirconium (Zr) as necessary, and a rare gas such as helium (He) gas, argon (Ar) gas, krypton (Kr) gas, or xenon (Xe) gas as a sputtering gas.
[0050] When the protective film 50 is made of a compound containing elements other than metal, it can be formed by reactive sputtering using a reactive gas such as an oxygen-containing gas, a nitrogen-containing gas, or a carbon-containing gas together with a rare gas as a sputtering gas. The target may also be a compound.
[0051] A hard mask film (an etching mask film of the absorber film 70 that functions as an etching mask when the absorber film 70 is dry-etched) 110 having etching characteristics different from those of the absorber film 70 may be provided on the side of the absorber film 70 away from the substrate 10, preferably in contact with the absorber film 70 (see FIG. 3). This hard mask film 110 is a film that functions as an etching mask when the absorber film 70 is dry-etched. After the absorber pattern is formed, this hard mask film 110 may be left as a part of the absorber film 70 as a reflectance reduction layer for reducing the reflectance at the wavelength of light used in an inspection such as a pattern inspection, or may be removed so as not to remain on the reflective mask. Examples of materials for the hard mask film 110 include materials containing chromium (Cr). The hard mask film 110 formed of a material containing chromium (Cr) is particularly suitable when the absorber film 70 is formed of a material containing tantalum (Ta) and not containing chromium (Cr). When a layer (reflectance reduction layer) 160, which mainly serves the function of reducing the reflectance at the wavelength of light used in inspection such as pattern inspection, is formed on the absorber film 70, the hard mask film 110 can be formed on the reflectance reduction layer 160 of the absorber film 70 (see FIG. 3). The hard mask film 110 can be formed by, for example, a magnetron sputtering method. The film thickness of the hard mask film 110 is not particularly limited, but is usually about 5 to 20 nm.
[0052] Furthermore, the reflective mask blank may have a resist film 170 formed on the side furthest from the substrate 10 (see FIG. 5). The resist film 170 is preferably an electron beam (EB) resist. EXAMPLES
[0053] The present embodiment will be specifically described below with reference to Experimental Examples, Examples, and Comparative Examples, but the present invention is not limited to the following Examples.
[0054] [Example 1] A 152 mm square, 6.35 mm thick low thermal expansion glass substrate (SiO 2 -TiO2 A back surface conductive film 30 was formed on a main surface of a tantalum (ZnO-based glass substrate) by DC pulse magnetron sputtering using a tantalum (Ta) target and a silicon (Si) target, with these targets facing the main surface of the substrate and the substrate being rotated.
[0055] Specifically, a tantalum (Ta) target and a silicon (Si) target can be mounted on a sputtering device capable of discharging the targets individually or two or more targets simultaneously, and each target was mounted on a substrate.
[0056] Then, while argon (Ar) gas (flow rate: 18 sccm) and nitrogen (N) gas (flow rate: 20 sccm) were flowing in the chamber, 1550 W of power was applied to the tantalum (Ta) target and 250 W of power was applied to the silicon (Si) target to form a 70 nm thick TaSiN backside conductive film 30. When the substrate shape after the backside conductive film was formed was measured, ΔTIR was -0.70 um and the sheet resistance was 45 Ω / □. Here, ΔTIR is expressed as a positive (+) when the change in the surface shape (warping) after the film is formed is a change in the concave direction compared to before the backside conductive film 30 is formed within a range of 142 mm square centered on the center of the main surface of the substrate, and a negative (-) when the change is a change in the convex direction (hereinafter, the positive and negative notations of ΔTIR in the backside conductive film formation in the examples are the same).
[0057] Next, the surface roughness of this film was measured using an AFM (atomic force microscope, JupiterXR manufactured by Oxford Instruments Ltd.), and the surface roughness Sq was found to be 0.22 nm.
[0058] The composition of this film was measured using XPS (X-ray photoelectron spectroscopy, Thermo Fisher Scientific K-ALPHA), and the nitrogen content was found to be 22 atomic %. When the silicon content in atomic % is CSi and the tantalum content in atomic % is CTa, CSi / (CTa+CSi) was 10%.
[0059] Next, in order to evaluate the risk of dust generation when this film is attached to and detached from the electrostatic chuck stage, a pattern was formed by the so-called magic lift-off method, and a simple test for scratches was carried out.
[0060] Specifically, a mark line of about 2 mm wide and 1 cm long was drawn in the center of a quartz substrate with a permanent marker, and then the quartz substrate was transported into a chamber, and a 70 nm TaSiN backside conductive film 30 was formed under the same conditions as above. After that, a cotton swab soaked in ethanol was pressed against the mark, and the film was peeled off together with the marker, while applying as little force as possible to the film surface, forming a pattern in which the film attachment area and the substrate were exposed. Next, a cotton swab also soaked in ethanol was pressed against the mark, and this time force was applied to rub the cotton swab around the pattern area for about 30 seconds, and then the substrate was observed from above with a single-view camera at a magnification of 3.5 times to see if there were any scratches on the pattern area.
[0061] Since no scratches were observed on the pattern under the conditions used in this experiment, the risk of dust generation during attachment and detachment of the stage is considered to be low.
[0062] [Example 2] In a chamber similar to that of Example 1, first, while flowing argon (Ar) gas (flow rate: 18 sccm) and nitrogen gas (flow rate: 25 sccm) in the chamber, a power of 1550 W was applied to the tantalum (Ta) target and a power of 250 W was applied to the silicon (Si) target to form a 70 nm thick TaSiN back surface conductive film 30. When the substrate shape after the back surface conductive film formation was measured, ΔTIR was −1.0 um and the sheet resistance was 64 Ω / □.
[0063] Next, the surface roughness of this film was measured by AFM, and the surface roughness Sq was found to be 0.45 nm.
[0064] When the composition of this film was measured by XPS analysis, the nitrogen content was 31 atomic %, and when the silicon content was CSi in atomic % and the tantalum content was CTa in atomic %, CSi / (CTa+CSi) was 10%. As in Example 1, a pattern was formed on a quartz substrate by magic lift-off and a simple test for scratches was performed, but no scratches were observed on the pattern under the conditions of this implementation. Therefore, it is considered that the risk of dust generation when attaching and detaching the chuck stage is low.
[0065] [Example 3] In a chamber similar to that of Example 1, first, while flowing argon (Ar) gas (flow rate: 18 sccm) and nitrogen (N) gas (flow rate: 15 sccm) in the chamber, a power of 1550 W was applied to the tantalum (Ta) target and a power of 250 W was applied to the silicon (Si) target to form a 70 nm thick TaSiN back surface conductive film 30. When the substrate shape after the back surface conductive film formation was measured, ΔTIR was −0.75 um and the sheet resistance was 37 Ω / □.
[0066] Next, the surface roughness of this film was measured by AFM, and the surface roughness Sq was found to be 0.21 nm.
[0067] When the composition of this film was measured by XPS analysis, the nitrogen content was 18 atomic %, and when the silicon content in atomic % was CSi and the tantalum content in atomic % was CTa, CSi / (CTa+CSi) was 10%. As in Example 1, a pattern was formed on a quartz substrate by magic lift-off, and a simple test for scratches was performed. Slight scratches were observed on the pattern, but the risk of dust generation when attaching and detaching the chuck stage is considered to be low.
[0068] [Example 4] In a chamber similar to that of Example 1, first, while flowing argon (Ar) gas (flow rate: 18 sccm) and nitrogen (N) gas (flow rate: 20 sccm) in the chamber, a power of 1050 W was applied to the tantalum (Ta) target and a power of 750 W was applied to the silicon (Si) target to form a 70 nm thick TaSiN back surface conductive film 30. When the substrate shape after the back surface conductive film formation was measured, ΔTIR was −0.49 um and the sheet resistance was 71 Ω / □.
[0069] Next, the surface roughness of this film was measured by AFM, and the surface roughness Sq was found to be 0.22 nm.
[0070] When the composition of this film was measured by XPS analysis, the nitrogen content was 25 atomic %, and when the silicon content was CSi in atomic %, and the tantalum content was CTa in atomic %, CSi / (CTa+CSi) was 42%. As in Example 1, a pattern was formed on a quartz substrate by magic lift-off, and a simple test for scratches was performed, but no scratches were observed on the pattern under the conditions of this implementation. Therefore, it is considered that the risk of dust generation when attaching and detaching the chuck stage is low.
[0071] [Example 5] In a chamber similar to that of Example 1, first, while flowing argon (Ar) gas (flow rate: 18 sccm) and nitrogen (N) gas (flow rate: 20 sccm) in the chamber, a power of 1550 W was applied to a tantalum (Ta) target and a power of 250 W was applied to a silicon (Si) target to form a TaSiN layer (first layer 31) having a thickness of 67 nm.
[0072] Subsequently, while flowing argon (Ar) gas (flow rate: 18 sccm), nitrogen (N) gas (flow rate: 20 sccm), and oxygen (O) gas (flow rate: 20 sccm) in the same chamber, a power of 1550 W was applied to the tantalum (Ta) target and a power of 250 W was applied to the silicon (Si) target to deposit a 3 nm-thick TaSiON layer (second layer 32) to form a multilayer back surface conductive film 30.
[0073] Next, the surface roughness of this film was measured by AFM, and the surface roughness Sq was found to be 0.21 nm.
[0074] When the composition of this film was measured by XPS analysis, the nitrogen content of the TaSiN layer (first layer 31) was 22 atomic %, CSi / (CTa+CSi) was 10%, and the total nitrogen and oxygen content of the TaSiON layer (second layer 32) was 53 atomic %, CSi / (CTa+CSi) was 15%.
[0075] As in Example 1, a pattern was formed on a quartz substrate by magic lift-off and a simple test for scratches was performed, but no scratches were observed on the pattern under the conditions of this experiment. The TaSiON layer on the surface is a film that is more likely to form microcrystals and an amorphous structure than the TaSiN layer, and the risk of dust generation when attaching and detaching the chuck stage is thought to be even lower.
[0076] [Comparative Example 1] In a chamber similar to that of Example 1, first, while flowing argon (Ar) gas (flow rate: 18 sccm) and nitrogen (N) gas (flow rate: 12.5 sccm) in the chamber, a power of 1550 W was applied to the tantalum (Ta) target and 250 W to the silicon (Si) target to form a TaSiN backside conductive film with a thickness of 70 nm. When the substrate shape after the backside conductive film formation was measured, ΔTIR was -0.74 um and the sheet resistance was 36 Ω / □.
[0077] Next, the surface roughness of this film was measured by AFM and found to be 0.20 nm.
[0078] The composition of this film was measured by XPS analysis, and the nitrogen content was found to be 17 atomic %, and when the silicon content in atomic % is CSi and the tantalum content in atomic % is CTa, CSi / (CTa+CSi) was 10%.
[0079] As in Example 1, a pattern was formed on a quartz substrate by magic lift-off and a simple test for scratches was performed. Under the conditions used in this experiment, scratches were observed on the pattern and film peeling occurred at the rubbed areas, indicating a high risk of dust generation when attaching and detaching the electrostatic chuck stage.
[0080] [Comparative Example 2] In a chamber similar to that of Example 1, first, while flowing argon (Ar) gas (flow rate: 18 sccm) and nitrogen (N) gas (flow rate: 30 sccm) in the chamber, a power of 1550 W was applied to the tantalum (Ta) target and 250 W to the silicon (Si) target to form a TaSiN backside conductive film with a thickness of 70 nm. When the substrate shape after the backside conductive film formation was measured, ΔTIR was -0.73 um and the sheet resistance was 848 Ω / □.
[0081] Next, the surface roughness of this film was measured by AFM, and the surface roughness Sq was found to be 1.1 nm.
[0082] When the composition of this film was measured by XPS analysis, the nitrogen content was 37 atomic %, and when the silicon content was CSi in atomic %, and the tantalum content was CTa in atomic %, CSi / (CTa+CSi) was 10%. As in Example 1, a pattern was formed on a quartz substrate by magic lift-off and a simple test for scratches was performed, but no scratches were observed on the pattern under the conditions of this implementation. However, as mentioned above, the sheet resistance was high at 848 Ω / □, and the surface roughness was rough, and there was a high risk of dust generation when attaching and detaching the electrostatic chuck stage, making it unsuitable as a backside conductive film.
[0083] [Comparative Example 3] In the same chamber as in Example 1, first, while flowing argon (Ar) gas (flow rate: 18 sccm) and nitrogen (N) gas (flow rate: 25 sccm) in the chamber, 800 W of power was applied to the tantalum (Ta) target and 1000 W of power was applied to the silicon (Si) target to form a TaSiN backside conductive film with a thickness of 70 nm. When the substrate shape after the backside conductive film formation was measured, ΔTIR was -0.61 um and the sheet resistance was 520 Ω / □.
[0084] Next, the surface roughness of this film was measured by AFM, and the surface roughness Sq was 0.3 nm. The composition of this film was measured by XPS analysis, and the nitrogen content was 30 atomic %, and when the silicon content in atomic % was CSi and the tantalum content in atomic % was CTa, CSi / (CTa+CSi) was 56%.
[0085] As in Example 1, a pattern was formed on a quartz substrate by magic lift-off and a simple test for scratches was performed, but no scratches were observed on the pattern under the conditions of this embodiment. However, the sheet resistance was high at 520 Ω / □, which is not a preferable embodiment from the viewpoint of good adsorption by an electrostatic chuck.
[0086] [Comparative Example 4] In the same chamber as in Example 1, first, 1800 W of power was applied only to the tantalum (Ta) target while flowing argon (Ar) gas (flow rate: 18 sccm) and nitrogen (N) gas (flow rate: 20 sccm) in the chamber, and a TaN backside conductive film with a thickness of 70 nm was formed. When the substrate shape after the backside conductive film formation was measured, ΔTIR was -2.18 um and the sheet resistance was 37 Ω / □.
[0087] Next, the surface roughness of this film was measured by AFM, and the surface roughness Sq was found to be 0.3 nm.
[0088] When the composition of this film was measured by XPS analysis, the nitrogen content was found to be 28 atomic %.
[0089] As in Example 1, a pattern was formed on a quartz substrate by magic lift-off and a simple test for scratches was performed. No scratches were observed on the pattern under the conditions of this experiment, but the film stress was large and the film was unsuitable as a backside conductive film.
Claims
1. A substrate; a multilayer reflective film provided on one surface of the substrate and reflecting at least EUV light; a back surface conductive film provided on the other surface of the substrate; Equipped with The back surface conductive film has a film thickness of 50 nm or more and less than 80 nm, contains tantalum (Ta), silicon (Si) and nitrogen (N), has a nitrogen content of 18 atomic % or more and less than 35 atomic %, and has a layer in which CSi / (CTa+CSi) is 3% or more and less than 50%, where CSi is the silicon content in atomic %, and CTa is the tantalum content in atomic %. Reflective mask blank.
2. The back surface conductive film is a first layer having a thickness of 50 nm or more and less than 80 nm, containing tantalum (Ta), silicon (Si) and nitrogen (N), the nitrogen content being 18 atomic % or more and less than 35 atomic %, and when the silicon content is CSi in atomic % and the tantalum content is CTa in atomic %, CSi / (CTa+CSi) is 3% or more and less than 50%; a second layer having a thickness of 3 nm or more and less than 10 nm, containing tantalum (Ta), silicon (Si), nitrogen (N) and oxygen (O), and having a total content of nitrogen and oxygen of 40 atomic % or more; The reflective mask blank according to claim 1 ,
3. the first layer is provided on the other surface of the substrate; The reflective mask blank according to claim 2 , wherein the second layer is provided on the other surface of the first layer.
4. The reflective mask blank according to claim 1 , wherein the back surface conductive film contains only tantalum (Ta), silicon (Si) and nitrogen (N).
5. 5. The reflective mask blank according to claim 1, wherein the back surface conductive film has only a layer having a thickness of 50 nm or more and less than 80 nm, containing tantalum (Ta), silicon (Si) and nitrogen (N), having a nitrogen content of 18 atomic % or more and less than 35 atomic %, and having a CSi / (CTa+CSi) of 3% or more and less than 50%, where CSi is the silicon content in atomic %, and CTa is the tantalum content in atomic %.
6. the first layer comprises only tantalum (Ta), silicon (Si) and nitrogen (N); The reflective mask blank according to claim 2 , wherein the second layer contains only tantalum (Ta), silicon (Si), nitrogen (N) and oxygen (O).
7. The reflective mask blank according to claim 2 or 6, wherein the rear surface conductive film has only the first layer and the second layer.
8. The back surface conductive film is The sheet resistance is 500 Ω / □ or less. The surface roughness (Sq) of the film is 0.5 nm or less, 3. The reflective mask blank according to claim 1, wherein, with respect to the other main surface of the substrate on which the back surface conductive film is formed, a change in warpage (ΔTIR) after the formation of the back surface conductive film relative to the warpage before the formation of the back surface conductive film is expressed as a plus (+) when it is a change in a concave direction and as a minus (-) when it is a change in a convex direction, ΔTIR, which is an index of film stress when the back surface conductive film is formed on the substrate, is -0.4 to -1.2 um.
9. A method for producing a reflective mask, comprising the step of producing the reflective mask by using the reflective mask blank according to claim 1 or 2.
Citation Information
Patent Citations
Reflecting type exposure mask, its manufacturing method and semiconductor element
JP2002246299A
Substrate with muti-layer reflective film, exposure reflection type mask blank, exposure reflection type mask, and manufacturing methods for these
JP2005210093A
Reflective mask blank and mask for exposure, substrate with multilayer reflection film, and process for fabricating semiconductor device
JP2008103481A
Substrate with multilayer reflection film for EUV lithography, reflective mask blank for EUV lithography, reflective mask for EUV lithography, and method of manufacturing semiconductor device
JP2013225662A
Substrate having multilayer reflection film, reflection type mask blank, reflection type mask and method for manufacturing semiconductor device
JP2021039271A